2017
DOI: 10.1097/hcm.0000000000000172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-management Education Through Telephone Follow-up in Diabetic Patients

Abstract: It is expected that the number of people living with diabetes rise especially in low- and middle-income countries. In Iran, more than four million adults have diabetes mellitus, and self-management education is essential for effective diabetes self-care. This study aimed to investigate the effect of self-management education with telephone follow-up in diabetic patients of rural areas of Fars province in Lamerd city, Iran. In this experimental study, 64 participants were randomly assigned to intervention and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Namjoo Nasab et al deployed a system wherein patients would attend four 90-minute educational sessions, and receive weekly phone calls from a trained nurse to discuss adherence to their self-care behaviours. At the end of the study period, the intervention group demonstrated significant improvements in fasting blood sugar and various DM self-management scores, when compared to a control group [37]. Investigators in Mexico established a system where patients received disease-specific information through a peer-led group educational session, as well as subsequent care management from a multidisciplinary healthcare team.…”
Section: Resultsmentioning
confidence: 99%
“…Namjoo Nasab et al deployed a system wherein patients would attend four 90-minute educational sessions, and receive weekly phone calls from a trained nurse to discuss adherence to their self-care behaviours. At the end of the study period, the intervention group demonstrated significant improvements in fasting blood sugar and various DM self-management scores, when compared to a control group [37]. Investigators in Mexico established a system where patients received disease-specific information through a peer-led group educational session, as well as subsequent care management from a multidisciplinary healthcare team.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from the current study suggest that health education, mobile clinics, and grassroots efforts such as the Multiplicadores program may facilitate the promotion of healthful behaviors to manage T2DM. Past studies that have focused on enhancing T2DM outcomes among adults living with T2DM in low- and middle-income countries 9,30 -36 have also identified similar strategies that enhanced T2DM health outcomes (ie, use of cultural tailoring, engaging community health workers, providing peer support). 9,30 -36 While addressing T2DM in the bateyes may be challenging and complex, novel interventions are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies that have focused on enhancing T2DM outcomes among adults living with T2DM in low-and middle-income countries 9,[30][31][32][33][34][35][36] have also identified similar strategies that enhanced T2DM health outcomes (ie, use of cultural tailoring, engaging community health workers, providing peer support). 9,[30][31][32][33][34][35][36] While addressing T2DM in the bateyes may be challenging and complex, novel interventions are still needed. Community-partnered research methods 37,38 seem prudent to overcome barriers and to enhance facilitators that may promote T2DM self-management and improve health outcomes for adults living with this disease in low-resourced communities.…”
Section: Fundingmentioning
confidence: 99%
“…The data collection instrument uses a questionnaire adopted from an existing questionnaire and has tested validity and reliability, to measure the family's ability to detect episodes of hypoglycemia. DSME applies guidelines, counseling, and behavioral interventions to improve knowledge of diabetes and the skills of individuals and families in managing DM [17]. The stages of activity: a.…”
Section: Methodsmentioning
confidence: 99%
“…However, 50-80% of diabetic patients did not have good ability and knowledge to self-care out their disease [16]. Therefore, diabetes self-management education (DSME) plays an important role in clinical management to reduce diabetes-related complications and premature deaths of diabetes [17].…”
Section: Introductionmentioning
confidence: 99%